STRATEGI PEMBELAJARAN AL-QUR’AN DALAM MENINGKATKAN SIKAP ISTIQOMAH MENGHAFAL AL-QUR’AN PESERTA DIDIK KELAS X NURUL FURQON MALANG - Nabilah Nabilah; Dian Mohammad Hakim; Dwi Fitri Wiyono (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Understanding the Al-Qur’an learning strategy is the steps that are arranged in a planned and systematic manner using certain techniques and methods in the Al-Qur’an learning process to achieve the desired goals. The researcher chose the location because the researcher wanted to know how the system of memorizing the Qur’an of students, the deposit system of students and how istiqomah of students in memorizing the Qur’an. This research is qualitative. Data were collected by observation, interviews, and documentation. As for data analysis, the author uses descriptive qualitative analysis, namely in the form of presenting written data regarding related data, both written and oral, from the object of research at the agency mentioned above, which has been observed, where in this case the author describes thoroughly about the situation. Which are actually. The results showed that the istiqomah of students memorizing the Qur’an at Nurul Furqon Malang showed promising results, using contextual strategies using lecture, question and answer methods, and experiments